Three-Dimensionally Printed Skin Substitute Using Human Dermal Fibroblasts and Human Epidermal Keratinocytes. Issue 5 (June 2021) - Patel, Jason; Willis, Joseph; Aluri, Akshay; Awad, Shadi; Smith, Metta; Banker, Zena; Mitchell, Morgan; Macias, Liz; Berry, Joel; King, Timothy
Abstract : Introduction: Wound healing affects millions of people annually. After injury, keratinocytes from the wound edge proliferate, migrate, and differentiate to recapitulate the 3-dimensional (3D) structure needed to provide a barrier function. If the wound is too large, skin grafting may be required. We are interested in discovering novel strategies to enhance the wound healing process. It may be possible to recreate a viable and histologically accurate skin tissue using 3D printing. We hypothesize that keratinocytes and dermal fibroblasts can be bioprinted into a viable skin substitute. Methods: Adult human dermal fibroblasts (HDFa) and adult human epidermal keratinocytes (HEKa) were cultured and subsequently printed with a 3D bioprinter within a hydrogel scaffold. After printing the HDFa and HEKa separately, cell viability and histological appearance were determined by sectioning the printed tissue and performing hematoxylin and eosin staining. The stained histological sections were analyzed for tissue morphology. Results: The HEKa and HDFa cells suspended in the hydrogel were successfully printed into 3D scaffolds that resembled skin with hematoxylin and eosin staining. Conclusions: The HEKa and HDFa cells can be grown on 3D-printed hydrogels successfully. In addition, HEKa and HDFa cells can survive and grow when suspended in a hydrogel and 3D printed. Future potential applications of these results could lead to the creation of viable skin tissue for wound healing and surgical repair.